Complex plant protein prepared from rice protein and pea protein: Improve the thermal stability of betanin. (February 2023) - Hu, Ting; Chen, Jun; He, Xuemei; Tang, Yayuan; Sun, Jian; Liu, Chengmei; Dai, Taotao
Graphical abstract: Highlights: Rice-pea complex plant protein highly improved the thermal stability of betanin. The main interaction between RP-PP and betanin was hydrophobic interaction. RP-PP had a porous network structure and aggregated after binding with betanin. The protective effect of RP-PP on betanin was due to its interaction and encapsulation. Abstract: Betanin (BN) is a kind of edible natural red pigment with a variety of biological activities, but the thermal instability of BN has critically restricted its application in food industry. In this study, complex plant protein (RP-PP) was constructed by rice protein (RP) and pea protein (PP) to study the thermal protection effect and protective mechanism on BN. Thermal degradation results indicated RP-PP significantly improved thermal protection effect, and the degradation rate of BN was decreased from 93.74 % to 56.48 % after heating at 80 ℃ for 60 min. The main interaction between RP-PP and BN was hydrophobic force based on the result of fluorescence spectroscopy, FTIR and molecular docking. In addition, a porous network structure of RP-PP was observed by SEM, and the pore structure gradually decreased at the presence of BN, which speculated BN was trapped in it. TEM observation showed that RP-PP gradually aggregated with the increasing BN concentration, leading to a significant increase in particle size and the formation of network structure. The BN acted as a bridge to the surrounding proteins in the aggregated complex and was encapsulated within it. The interaction and encapsulation may be the key reasons for the improved thermal stability of BN.